2023
DOI: 10.3390/horticulturae9070749
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Agricultural Land Use on Nematode Diversity and Soil Quality in Dalmada, South Africa

Abstract: During a survey on soil nematode diversity, the soil samples were collected from Field-1 (3-months-not-used land), Field-2 (5-years-not-disturbed land), Field-3 (the rhizosphere of tomatoes), and Field-4 (natural land, not disturbed for 50 years), in Dalmada, Limpopo Province, South Africa. A total of 25 nematode genera were found to be associated with the surveyed plant species. The result showed Acrobeloides, Aphelenchus, Aporcella, Ditylenchus, Mesorhabditis, Pratylenchus, and Rotylenchus with a 100% freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Ammonium (NH 4 + ) was shown to have a positive (Rotylenchus) or negative (Rotylenchulus) correlation with plant-parasitic nematodes [5]. The same result was obtained in the present study with a positive correlation between NH 4 + and Rotylenchus.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Ammonium (NH 4 + ) was shown to have a positive (Rotylenchus) or negative (Rotylenchulus) correlation with plant-parasitic nematodes [5]. The same result was obtained in the present study with a positive correlation between NH 4 + and Rotylenchus.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have delved deep into the influence of the chemical properties of soils affecting plant vigor and consequently affecting the distribution and population density of nematodes. These studies have shown that chemical composition significantly regulates nematode population dynamics by affecting plant health and productivity [5,21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations